Representasi Aktor Sosial dalam Pemberitaan BBC Arabic tentang Serangan Israel terhadap Iran - Meki Polanda (PRASASTI: Journal of Linguistics, 2026)
The conversation about Israel's attack on Iran is an interesting topic and has become the center of attention by the mass media, because it has a high enough value to be reported. The purpose of this study is to identify the representation of social actors in BBC Arabic's reporting on Israel's attack on Iran using Theo van Leeuwen's critical discourse analysis model. The approach used in this study is a descriptive qualitative method. The primary data source that became the basis for the research was taken from the BBC Arabic website which contained news about Israel's attack on Iran on June 13, 2025. The data collection technique used in this study was the listening and note-taking method. The results of the study show that BBC Arabic presents news by presenting the dominant party, namely Israel, and the marginalized party, namely Iran. However, BBC Arabic still strives to present balanced and comprehensive news by displaying the names of victims as a result of the Israeli attack. BBC Arabic constructs social actors in the news about Israel's attack on Iran by bringing them up, obscuring them, and eliminating them through strategies of differentiation, objectivation, abstraction, categorization, determination, and assimilation.